The Significance of Vocational-Technical Education in World-Wide Development - Worthington, Robert M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Vocational-technical education must be viewed within the framework of total national goals of education and, combined with socioeconomic planning, considered as part of the total development scheme of a nation. One of its immediate purposes is performing a key support role in worldwide economic development and stability. Since economic and educational disadvantage overlap considerably, some nations integrate their literacy efforts with national development efforts such as vocational and technical training. During the 1980s, the United States will have to deal with four dimensions of change that will coincide directly with the changes in worldwide development--economic, technological, demographic, and governance. Vocational education plays a formidable role in any positive response to them, since education and work will have to be interwoven for all persons. The transition from school to work must be made easier, as the reverse transition--from work back to school--is accepted as commonplace. The pace of technological change is accelerating, and industrialized countries must learn to teach individuals how to learn and to obtain skills to do what they have not been specifically trained to do. A continual international dialogue and sharing of these ideas will foster worldwide development. (YLB)
ERIC Note: Presented at the International Conference on Establishing Technical and Vocational Education Programs with Developing Countries (Racine, WI, April 26, 1983).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cooperation; Developed Nations; Developing Nations; Economic Development; Educational Development; International Relations; Outcomes of Education; School Role; Vocational Education; Opinion Papers; Speeches/Meeting Papers